A novel approach to standardizing landing and balancing tasks in netball using single-leg horizontal jumps. Issue 4 (2nd October 2018) - Humphries, Brendan; Stanton, Robert; Hayman, Melanie; Borgelt, Hanna; Scanlan, Aaron
ABSTRACT: This study aimed to establish the reliability of a novel netball task using a single-leg horizontal jump (SLHJ). Twenty-five females 18–39 years performed SLHJs for maximal displacement and ground-reaction forces. Participants completed two trials for each leg on two occasions separated by 6 weeks of pre-season netball training. Paired sample t tests highlighted no significant differences within trials for either limb. Significant ( p ≤ .05) changes are reported for displacement, and dominant and nondominant X and Y forces, after 6-week netball training. SLHJ displacement showed excellent within-session reliability at baseline for dominant (intraclass correlation coefficient (ICC(2, 1)) = 0.922, 95% confidence interval (CI) 0.826–0.966) and nondominant (ICC(2, 1) = 0.925; 95% CI 0.832–0.967) landings. At 6 weeks, within-session reliability remained excellent for dominant (ICC(2, 1) = 0.967, 95% CI 0.926–0.985) and nondominant ICC 0.968 (95% CI 0.929–0.986) landings. The reliability of the single-leg horizontal jump task for netball remained strong after 6 weeks of netball training.